Epidemiological characteristics of women with cervical erosion in Al-Sader city, Baghdad, Iraq. - Al-Kaseer, Eman A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Cervical erosion (CE) is a common finding on routine pelvic examination during the fertile years. Published articles on CE in Iraq are scarce; therefore this study was carried out. Methods: A total of 100 non pregnant women had CE attending a private clinic in Al-Sader city, Baghdad, was included in this study. Pelvic examination was done; demographic data and gynaecological history were obtained. Results: The age of women was 27.1 ± 5.9 years with 7.3 ±2.9 educational years. Mucopurlent vaginal discharge was a complaint in 49% of women, and a watery vaginal discharge was a complaint in a similar percent. Thirty four of women were oral contraceptive users and 11% were using intrauterine contraceptive device. Women had equal or more than 4 children constituted 90%. Conclusion: women with CE were at fertile age, had an early marriage and a high party and with a low educational status. The symptoms were vaginal discharge (mucopurlent or watery) and backache. Women with CE were either current or recent oral contraceptives users or using IUCD